Democratic development in East Asia - Shelley, Becky (RoutledgeCurzon / Taylor & Francis Group, 2005)
Democratic Development in East Asiaexplores an important but neglected topic in the literature on democratization in East Asia: the international dimension of democratization. It presents a coherent and comprehensive analysis of the impact of external political, economic and cultural factors on China, South Korea and Taiwan's political development since World War II. The author analyzes the circumstances under which the international context affects domestic actors' choice of political institutions and actions and concentrates on a selection of key international structures and actors that make up this complex picture. Shelley also examines the international political economy, aspects of the United Nations system, diffuse cultural factors and processes, democracy movements, and a number of international non-government organizations.